Historical reality and person from Xavier Zubiri and Ignacio Ellacuría - Vilches Vilches, Daniel; Zuchel, Lorena (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
This article analyzes and shows the elaboration of the notion of historical reality and its relationship with personal reality from the thoughts of Xavier Zubiri and Ignacio Ellacuría. Two conceptual discrepancies between both philosophers are identified. Firstly, in relation to the possibility of creating content and formality of reality and, secondly, in relation to the ultimacy of historical reality with respect to the person. The work presents a conciliatory way to show how both discrepancies are overcome through a cyclical and complementary conception.
Keywords: history; person; Xavier Zubiri; Ignacio Ellacuría